Representatives Of Sufi Schools In Khorezm - Nargiz Xudaykulova (Periodica Journal, 2025)
The article is devoted to the emergence of Sufi schools and the active development of the theory and practice of Sufism in the territory of the Khorezm oasis. The article highlights the arguments of a number of Sufi thinkers, such as Najmiddin Kubro (1145-1221), a major Khorezm scholar and fanatic who left a deep mark on the development of mysticism in the 13th century, Az-Zamakhshari, the author of Al-Kashshaf, which many scholars in the modern world study the Koran based on this work.., Sheikh Odina Eshon known as Odina Eshon, is Abul-Muzaffar ibn Sayyid Muzaffar al-Husayni AlKhorezmi Al-Karwaki, who enters the world of science with his famous legacies such as “The World'At ul-Abidin” and "Tabbat uttoyibin". The thoughts of these scientists about spirituality and spiritual culture, set out in the framework of ethics, education, and moralizing, are subject to scientific research.
Keywords: sect; upbringing; thinker